Curved surface turbulence precision machining method for artificial joint complex of titanium alloy. (November 2015) - Zhang, L.; Deng, B.; Xie, Y.; Zhang, R.; Ji, S.; Wen, D.
Abstract : Titanium alloy is widely used in the design of artificial joints because of its high strength and low modulus. But, titanium alloy has its defects such as poor machinability, low thermal conductivity. The surface of artificial joints is usually complex curved surface, which makes that high surface quality cannot be easily obtained by using conventional processing methods. Aiming at the processing problems for the complex surface of titanium alloy artificial joints, a partial coverage constraint style complex surface turbulence precision machining method is proposed for titanium alloy artificial joint. The partial covering surface binding component is established by profiling of the artificial joint surface, so the controlled flow channel of abrasive flow is built. The processing surface is a part of the flow channel wall, which making abrasive flow into the turbulent fully developed state. The micro-cutting of the processing surface is realised by the disorderly movement of the abrasive to reach the mirror-level surface roughness. The experiment results show the effectiveness and feasibility of this method.